Seating among the giants: A study of South Africa’s pursuit of the African agenda and voting behaviour in the United Nations Security Council - De Lamare, Nelson (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.